Dampak Perceraian Terhadap Hubungan Orang Tua Dan Anak: Studi Pada Keluarga Pasca-Perceraian - Dhia Zahwa Fadhiela Andriani; Izzanil Hidayati; Nadila Yosvita; Nur Aisyah Arsya; Shalaisya Adna Azzahra; Azizah Azzahra; Laila Septi Amalia Putri (CV. ITTC INDONESIA, 2026)
Divorce is a social phenomenon that fundamentally alters family structure, communication patterns, and the emotional dynamics between parents and children. This study aims to examine the impact of divorce on parent-child relationships in post-divorce families, focusing on communication changes, emotional closeness, fulfillment of children’s emotional needs, and family conflict resolution. A qualitative approach with a descriptive case study method was employed. The primary subject was a 16-year-old female adolescent whose parents divorced five years ago, with her mother serving as a supporting informant. Data were collected through semi-structured in-depth interviews and non-participatory observation, then analyzed thematically using Miles et al.’s (2014) interactive analysis model. Triangulation of sources was applied to ensure data validity. The findings revealed five main themes: (1) the family relationship before and after divorce was perceived positively by the subject, as divorce reduced daily conflict; (2) communication with the non-custodial parent (father) declined significantly over time due to unresolved emotional trauma; (3) emotional openness was predominantly directed toward the mother, who functioned as both a confidant and emotional support figure; (4) the mother was the primary source of emotional support, whereas the father’s involvement was minimal and marked by coercion regarding future academic choices; and (5) family conflict resolution prior to divorce relied heavily on the maternal extended family. These findings underscore that the quality of post-divorce parenting and the maintenance of supportive communication are critical determinants of children’s psychological adjustment following parental separation.